Solid state dye sensitized solar cells - Chen, Nathaniel Zhengwei. (2013)
Several recent advances in the design in acceptors and hole transport materials have allowed for record power conversion efficiencies. (CH3NH3)PbI3 perovskite nanocrystals have proven to be a high and effective absorber of light. Solid state devices allow for better manufacturability and create a larger open-circuit voltage. A high power conversion efficiency are significant targets for practical applicat0ions of solid state solar cells, by changing the thicknesses of various layers, we can find out the impacts it creates. For the blocking layer, a thinner and compact layer was needed also. A study using thinner film of TiO2 was performed, the thickness varied from 1.2 μm to 0.3μm by using α-Terpineol as the solvent and it was seen that the optimal thickness was 0.6 μm. A thinner film of spiro-OMeTAD was created by increasing the spin speed, finally all the experiments improved the cell and an efficiency of 3.13% was achieved.